Decadal Prediction Large Ensemble Project - Steve Yeager Yeager@Ucar.Edu (UCAR/NCAR Earth System Grid, 2018)
The CESM Decadal Prediction Large Ensemble (DPLE) is a set of simulations carried out at NCAR to support research into near-term Earth System prediction. The DPLE comprises 62 distinct ensembles, one for each of 62 initialization times (November 1 of 1954, 1955, ..., 2014, 2015). For each start date, a 40-member ensemble was generated by randomly perturbing the atmospheric initial condition at the round-off level. The simulations were integrated forward for 122 months after initialization. Observation-based ocean and sea ice initial conditions for the 1954-2015 period were obtained from a reanalysis-forced simulation of the CESM ocean and sea ice models. The initial conditions for the atmosphere and land models were obtained from CESM Large Ensemble (LENS) simulations at corresponding historical times. Full field initialization was used for all component models, and so drift adjustment prior to analysis is generally recommended (e.g., see here). The DPLE was run using the same CESM code base, configuration details, component resolutions (nominally 1-degree in both atmosphere and ocean), and external forcing datasets as for the CESM LENS project. DPLE therefore represents the "initialized" complement to the LENS simulations. Steve Yeager [yeager@ucar.edu] at NCAR is the primary contact for DPLE-related inquiries. Nan Rosenbloom and Gary Strand were instrumental in the setup, running, and post-processing of the DPLE simulations, with assistance from Sheri Mickelson, Alice Bertini, Jim Edwards, and Shiquan Su. The initial 10 members were made possible by a Department of Energy award of computer time on machines at the National Energy Research Scientific Computing Center (NERSC). The additional 30 members were completed in early 2017 thanks to a CISL Accelerated Scientific Discovery award on Cheyenne. The DPLE is a CESM community project, and the output from the simulations is available to anyone who is interested. Monthly, daily, and 6-hourly outputs are archived on the NCAR HPSS system and accessible from the Earth System Grid (http://www.earthsystemgrid.org) as single variable timeseries. A list of available output fields can be found here. (NOTE: Not all fields are available for all 40 members. See Known Issues link for further details.) If you are interested in in analyzing the CESM-DPLE, we kindly ask that you provide a short description of your proposed research focus to Steve Yeager [yeager@ucar.edu] to be included in the list of ongoing projects (see sidebar). An overview article describing the DPLE has been published in the Bulletin of the American Meteorological Society: Yeager, S. G., G. Danabasoglu, N. Rosenbloom, W. Strand, S. Bates, G. Meehl, A. Karspeck, K. Lindsay, M. C. Long, H. Teng, and N. S. Lovenduski, 2018: Predicting near-term changes in the Earth System: A large ensemble of initialized decadal prediction simulations using the Community Earth System Model, Bulletin of the American Meteorological Society, , doi: . Please reference this paper in oral presentations and papers that make use of CESM-DPLE data and acknowledge the supercomputing resources provided by DOE/NERSC as well as NSF/CISL/Cheyenne. A list of publications using the DPLE data (along with closely related publications that made use of earlier versions of the CESM decadal prediction system) can be found at the Publications link on the sidebar. If you would like to add a publication to this list, please contact [yeager@ucar.edu].